PENGARUH HARGA DIRI (SELF-ESTEEM) TERHADAP RESILIENSI ANAK BINAAN DI LPKA KELAS I KUTOARJO - Murti, Gading Wisnu; Wibowo, Padmono (Universitas Nusa Cendana, 2024)
Self-esteem and resilience are two psychological concepts that can influence each other, especially in correctional foster children. In this context, self-esteem refers to the level of self-esteem or confidence of correctional foster children in their own abilities and self-worth, while resilience refers to the ability of fostered children to overcome challenges, pressures, or trauma and recover well. This study was conducted with the aim of determining the influence of Self-Esteem on the Resilience of Assisted Children at the Kutoarjo Class I Special Child Development Institute. The research method used is a quantitative research method using primary data from questionnaires distributed through non-probability sampling techniques with saturated sampling or total sampling to all Assisted Children at the Special Development Institute for Class I Children in Blitar as many as 80 people. The questionnaire contains 50 items of statements related to research variables, which are then analyzed by descriptive analysis tests, simple linear regression tests, significance tests and determination tests using the help of IBM SPSS 25 software. The results showed that there is a positive and significant relationship between Self-Esteem and Resilience in the Kutoarjo Class I Special Child Development Institute. Keywords: Self-Esteem; Resilience; Juvenile Correctional Facility